Experimental investigation of shear deformation in normal reinforced concrete beams - Chen, Raymond Hock Yew (Nanyang Technological University, 2023)
Shear deformation significantly impacts the safety and overall performance of reinforced concrete beam, constituting a critical element in their structural behaviour. The primary objective of this study is to enhance our knowledge regarding shear deformation in reinforced concrete beams by conducting a methodical and exhaustive examination.